Hedgehog Signaling: Linking Embryonic Lung Development and Asthmatic Airway Remodeling - Ling-Hui Zeng; Muhammad Qasim Barkat; Shahzada Khurram Syed; Shahid Shah; Ghulam Abbas; Chengyun Xu; Amina Mahdy; Nadia Hussain; Liaqat Hussain; Abdul Majeed; Kashif-ur-Rehman Khan; Ximei Wu; et al. (Cells, 2022)
The development of the embryonic lung demands complex endodermal–mesodermal interactions, which are regulated by a variety of signaling proteins. Hedgehog (Hh) signaling is vital for lung development. It plays a key regulatory role during several morphogenic mechanisms, such as cell growth, differentiation, migration, and persistence of cells. On the other hand, abnormal expression or loss of regulation of Hh signaling leads to airway asthmatic remodeling, which is characterized by cellular matrix modification in the respiratory system, goblet cell hyperplasia, deposition of collagen, epithelial cell apoptosis, proliferation, and activation of fibroblasts. Hh also targets some of the pathogens and seems to have a significant function in tissue repairment and immune-related disorders. Similarly, aberrant Hh signaling expression is critically associated with the etiology of a variety of other airway lung diseases, mainly, bronchial or tissue fibrosis, lung cancer, and pulmonary arterial hypertension, suggesting that controlled regulation of Hh signaling is crucial to retain healthy lung functioning. Moreover, shreds of evidence imply that the Hh signaling pathway links to lung organogenesis and asthmatic airway remodeling. Here, we compiled all up-to-date investigations linked with the role of Hh signaling in the development of lungs as well as the attribution of Hh signaling in impairment of lung expansion, airway remodeling, and immune response. In addition, we included all current investigational and therapeutic approaches to treat airway asthmatic remodeling and immune system pathway diseases.